96.3k views
2 votes
Which equation shows the result of substituting y from the first quation into the second equation for the given system ? Y = x + 5 y - 2x = 2

2 Answers

5 votes

Answer:

see explanation

Explanation:

substituting y = x + 5 into y - 2x = 2, gives

x + 5 - 2x = 2


User Chris Talman
by
4.9k points
7 votes

Answer:


x+5-2x=2


5-x=2

Explanation:


y = x + 5


y - 2x = 2

substituting y from the first equation into the second equation

We are given with first equation
y = x + 5

We plug in x+5 for y in second equation


y - 2x = 2, Replace y with x+5


x+5-2x=2

combine like terms

x-2x is -x


5-x=2

User Ivanicus
by
4.9k points